Retrofitting the built environment - Swan, William, 1972- (Wiley-Blackwell, 2013)
"Retrofitting the Built Environment is an extension of this conference. Contained within is a mix of policy, technical and social science papers, presented by both academic and industry authors, giving a multiple perspective of the issue from both a UK and international perspective"--